Utilization of Waste Frying Oil as A Source of Carbon in The Production of Biosurfactant using Exiguobacterium profundum - Irma Mardiah; Kartika Puspitaningrum; Syarif Hamdani; Nur Asni Setiani (Future Science)
Biosurfactant is a secondary metabolite produced by microorganisms that can be used as an alternative to environmentally friendly surfactants. Exiguobacterium profundum is one of the biosurfactants producers that potentially to be used in the pharmaceutical field. The use of waste frying oil as a carbon source can be used as a solution in overcoming the high cost of producing biosurfactants. The purpose of this study was to obtain optimum conditions in the production of biosurfactants by utilizing waste frying oil as a carbon source. In this study, variations in the optimized production conditions included the concentration of waste frying oil, labeled 2%, 3%, 4%, and 5%, and the medium pH at 6, 7, and 8. The study was using Mineral Salt Medium as production medium, the amount of inoculum concentration was 10% v/v, agitation speed 160 rpm, and incubation at room temperature. The optimum conditions for biosurfactant production were determined based on the best emulsification index. The biosurfactant extraction was carried out using a combination of chloroform and methanol (2:1) solvents. The best concentrations of waste frying oil for Exiguobacterium profundum was 5%, and the best medium pH was 7. Biosurfactants produced from Exiguobacterium profundum amounted to 8,2 g/L with an emulsification index 63,2%.